Adult patients with acute lymphoblastic leukemia and molecular failure display a poor prognosis and are candidates for stem cell transplantation and targeted therapies - Gökbuget, Nicola; Bartram, Claus R. (Blood, 2012)
Quantification of minimal residual disease (MRD) by real-time PCR directed to TCR and Ig gene rearrangements allows a refined evaluation of response in acute lymphoblastic leukemia (ALL). The German Multicenter Study Group for Adult ALL prospectively evaluated molecular response after induction/consolidation chemotherapy according to standardized methods and terminology in patients with Philadelphia chromosome-negative ALL. The cytologic complete response (CR) rate was 89% after induction phases 1 and 2. At this time point the molecular CR rate was 70% in 580 patients with cytologic CR and evaluable MRD. Patients with molecular CR after consolidation had a significantly higher probability of continuous complete remission (CCR; 74% vs 35%; P < .0001) and of overall survival (80% vs 42%; P = .0001) compared with patients with molecular failure. Patients with molecular failure without stem cell transplantation (SCT) in first CR relapsed after a median time of 7.6 months; CCR and survival at 5 years only reached 12% and 33%, respectively. Quantitative MRD assessment identified patients with molecular failure as a new high-risk group. These patients display resistance to conventional drugs and are candidates for treatment with targeted, experimental drugs and allogeneic SCT. Molecular response was shown to be highly predictive for outcome and therefore constitutes a relevant study end point. The studies are registered at www.clinicaltrials.gov as NCT00199056 and NCT00198991.